SEJARAH PENDIDIKAN ISLAM : PERSPEKTIF PEMIKIRAN IBNU KHOLDUN DAN RELEVANSINYA DENGAN PENDIDIKAN DI INDONESIA - Uluwiyah, Tarbyatul (UIN Antasari Banjarmasin, 2023)
Regarding education, there are many thoughts from scholars regarding education for humans, both Islamic scholars and non-Islamic scholars. Thoughts of experts on education are very diverse, but there are many thoughts in common. In this paper the author will analyze one educational thought, namely the thought of an Islamic scholar whose work is very famous entitled Muqadimah, namely Ibnu Kholdun. This paper will explain the history of Islamic education according to Ibn Kholdun's thoughts, and how relevant it is to the current era in Indonesia. In this problem, the author uses a qualitative method in searching data related to the theme. The data taken is in the form of relevant journals or books. Ibn Khaldun was a thinker who was very firm in his faith and committed to religious teachings. Ibn Khaldun proportionally places authority and reason, in contrast to previous thinkers. He was reluctant to mix things up or to link things up with religious rules, which were usually coercive. Ibn Khaldun only wanted to see the world through scientific reasoning. So from that Aristotle's concept of logic regarding logic can be used as a basis, while his concept of divinity according to Ibn Khaldun's view cannot be used as a strong basis. For this reason, it is important for the author to know how Ibn Kholdun's thoughts look at the history of Islamic education and its relevance to education in Indonesia.